Transcriptional repression of SKP2 is impaired in MYCN-amplified neuroblastoma - Muth, Daniela; Ghazaryan, Seda; Eckerle, Isabella; Beckett, Emily; Pöhler, Christina; Batzler, Julia; Beisel, Claudia; Gogolin, Sina; Fischer, Matthias; Henrich, Kai-Oliver; Ehemann, Volker; Gillespie, Paul; et al. (Cancer research, 2010)
The cell cycle regulator, SKP2, is overexpressed in various cancers and plays a key role in p27 degradation, which is involved in tumor cell dedifferentiation. Little is known about the mechanisms leading to impaired SKP2 transcriptional control in tumor cells. We used neuroblastoma as a model to study SKP2 regulation because SKP2 transcript levels gradually increase with aggressiveness of neuroblastoma subtypes. The highest SKP2 levels are found in neuroblastomas with amplified MYCN. Accordingly, we found 5.5-fold (range, 2-9.5) higher SKP2 core promoter activity in MYCN-amplified cells. Higher SKP2 core promoter activity in MYCN-amplified cells is mediated through a defined region at the transcriptional start site. This region includes a specific E2F-binding site that makes SKP2 activation largely independent of mitogenic signals integrated through the SP1/ELK-1 site. We show by chromatin immunoprecipitation that SKP2 activation through the transcriptional start site in MYCN-amplified cells is associated with the low abundance of pRB-E2F1 complexes bound to the SKP2 promoter. Transcriptional control of SKP2 through this regulatory mechanism can be reestablished in MYCN-amplified cells by restoring pRB activity using selective small compound inhibitors of CDK4. In contrast, doxorubicin or nutlin-3 treatment—both leading to p53-p21 activation—or CDK2 inhibition had no effect on SKP2 regulation in MYCN-amplified cells. Together, this implies that deregulated MYCN protein levels in MYCN-amplified neuroblastoma cells activate SKP2 through CDK4 induction, abrogating repressive pRB-E2F1 complexes bound to the SKP2 promoter. Cancer Res; 70(9); 3791-802. ©2010 AACR.
Gesehen am 17.05.2023